First report of wilt disease in cashew (Anacardium occidentale L.) caused by Fusarium decemcellulare in Kerala, India - A. V. Meera Manjusha; P. K. Laya; Amal Premachandran; M. Veena (CABI Agriculture and Bioscience, 2023)
Abstract Background The incidence of wilt disease of cashew (Anacardium occidentale L.) caused by Fusarium sp. has recently emerged in two-year-old cashew trees in an experimental field at the Regional Agricultural Research Station, Pilicode, in the Kasaragod district of Kerala, India. The disease was characterized initially by chlorosis of foliage and shoots, followed by necrosis and wilting, with internal symptoms including vascular necrosis, eventually resulting in complete plant mortality. Methods A fungal pathogen was isolated repeatedly from the infected vascular tissues onto potato dextrose agar medium. Symptomology, cultural, morphological and molecular studies were performed to characterize the pathogen causing the disease. Results In culture, the colony of fungus was white, later turning pink. The fungus produced both macro and micro conidia in culture. Molecular characterization revealed the identity of the isolates as Fusarium decemcellulare Brick. Pathogenicity of the isolate was confirmed in cashew seedlings, thereby demonstrating Koch’s postulates. Conclusion To our knowledge, this is the first record of wilt disease of cashew caused by F. decemcellulare in India. The culture of the fungus has been deposited with the National Fungal Culture Collection of India at Agharkar Research Institute, Pune, India with accession number NFCCI 4801, and sequence of the fungus was deposited at GenBank of NCBI with accession number OP942472.